Tratti e deserti. Deleuze e l’immagine-affezione - Godani, Paolo (Scenari, 2024)
The purpose of this article is to contextualize the notion of affection-image, as presented in Cinema 1: The Movement-Image, within Deleuze’s thinking system. In the first place, we will try to show how the two elements that make up affection-image, face anérimentale de ses techniques et de ses prod any-spaces-whatsoevers, refer respectively to «faciality» traits (traits de visagéité) and landscape traits (traits de paysage) – which is spoken about both in Proust and Signs and in A Thousand Plateaus. Secondly, it will be shown how both these elements relate to the fundamental notion of event, as described in The Logic of Sense.